Crian??as em cena: subjetividade, inf??ncia e educa????o infantil - Pisaneschi, Lucilene Schunck Costa (2019)
The current research brings as object of study the child subjectivity having as guiding element the following inquiry: how do the socio-cultural relations interfere on the construction of this subjectivy? Given the purpose of understanding the correlation between social and cultural objectivity produced within the children???s school and the course of child individuation, we establish as specific objectives: understand the role of the Cultural Industry facing the denial of child subjectivity; apprehend the involved elements in the school of child education that have been denying the individuation of the little ones; and identify the opposition produced by the children in front of this elements that have been denying their subjectivation The main assumption of this thesis is the one that the school of children works as a privileged instrument on the process of the construction of the child subjectivy. This assumption made us come to the following hypothesis: The Cultural Industry creating mechanisms that put the children on the grown-up???s universe by the consumption works in a forceful way on the denial of the child subjectivy; in the environment of the children???s school, the trend that has been dictating the socio-cultural relations between them and the adults is the denial of this subjectivity of the children. In the theoretical-methodological perspective, we based ourselves on the Critical Theory of Society, mainly on the contributions of researchers from the first generation of The Frankfurt School. The methodological procedures had as a scope the observation done in an Elementary School in the city of Sao Paulo. This observation can be seen on the essay by scenes of the daily routine of the school that showed us the ambiguities of the related procedures developed there. The investigative path revealed us the mechanisms by which the cultural industry has been acting on the denial of the child subjectivity; the ways the socio-cultural relations established on the daily routine support the tendency of the denial of the child subjectivy and finally demonstrate the ways of resistance produced by the children facing the situations the deny their individualities. By having their subjectivies denied, the children build inside their own denial, transgression and subversion actions that illustrate the continuous path of construction-deconstruction-reconstruction of the child individuality.